1982
DOI: 10.1172/jci110520
|View full text |Cite
|
Sign up to set email alerts
|

Studies in porphyria: functional evidence for a partial deficiency of ferrochelatase activity in mitogen-stimulated lymphocytes from patients with erythropoietic protoporphyria.

Abstract: A B S T R A C T In this paper we show that the ferrochelatase defect in erythropoietic protoporphyria (EPP) can readily be identified in mitogen-stimulated lymphocytes since such cells from patients with EPP accumulate approximately twice as much protoporphyrin IX as cells from normal subjects when incubated with a porphyrin precursor, 6-aminolevulinic acid (ALA). Treatment of cultures with ALA and with the iron chelator, CaMgEDTA significantly increased the level of protoporphyrin IX in mitogen-stimulated lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
8
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 24 publications
4
8
0
Order By: Relevance
“…Although the parents were available for ferrochelatase assays in an early study, they and several other members of this family were no longer available for the molecular studies on the ferrochelatase defect, for reasons beyond our control. Partial ferrochelatase deficiency (-50%) is also known to occur in both asymptomatic carriers and clinically affected patients in other EPP families (6,14). Thus the occurrence of '50% ferrochelatase deficiency both in the father and in the daughter is similar to that in other EPP families and is compatible with an autosomal dominant inheritance of EPP in this family.…”
supporting
confidence: 68%
See 3 more Smart Citations
“…Although the parents were available for ferrochelatase assays in an early study, they and several other members of this family were no longer available for the molecular studies on the ferrochelatase defect, for reasons beyond our control. Partial ferrochelatase deficiency (-50%) is also known to occur in both asymptomatic carriers and clinically affected patients in other EPP families (6,14). Thus the occurrence of '50% ferrochelatase deficiency both in the father and in the daughter is similar to that in other EPP families and is compatible with an autosomal dominant inheritance of EPP in this family.…”
supporting
confidence: 68%
“…In humans, EPP is thought to be an autosomal dominant disease, but the frequency of its clinical expression is highly variable (2). Previous studies have shown that, in patients with EPP, the activity of ferrochelatase (protoheme ferro-lyase, EC 4.99.1.1) is decreased to -50% compared with normal levels, in all tissues and isolated cell preparations so far examined: e.g., bone marrow (3), liver (4), cultured skin fibroblasts (5), and lymphoblasts (6). A deficiency of ferrochelatase activity is consistent with the marked increase in protoporphyrin IX, a substrate for the enzyme, observed in erythrocytes, plasma, and liver of patients with EPP, and accounts for cutaneous photosensitivity in this disorder.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The former is a spe cific inhibitor of ferrochelatase in various types of cultured cells [7,9,11], while the lat-ter is one of the two substrates of ferrochelatase; the other substrate of the enzyme is pro toporphyrin. Our results indicate that iron decreased porphyrin levels, and this decrease was partially reversed by CaMg EDTA (fig.…”
Section: Discussionmentioning
confidence: 99%